Efficacy and Safety of Bullectomy versus Conservative Management in Patients with Symptomatic Vanishing Lung Syndrome: A Systematic Review and Meta-Analysis of Respiratory Outcomes - Raisya Farah Monica; Oea Khairsyaf; Dessy Mizarti (HM Publisher, 2025)
Background: Vanishing lung syndrome (VLS), a severe form of giant bullous emphysema, causes debilitating dyspnea by compressing functional lung. A critical evidence gap exists regarding the optimal management strategy, forcing a contentious choice between surgical bullectomy and conservative care. This study provides the first meta-analytic synthesis comparing these two approaches. Methods: Following PRISMA guidelines, we systematically searched PubMed, Embase, Scopus, and Web of Science for comparative studies (2015-2024) evaluating bullectomy versus conservative management in symptomatic VLS. Primary outcomes were changes in Forced Expiratory Volume in one second (FEV1), St. George's Respiratory Questionnaire (SGRQ) scores, and major complications. Data were pooled using a random-effects model, and bias was assessed with the ROBINS-I tool. Results: Six non-randomized studies involving 488 patients were included. The overall risk of bias was moderate to serious. Compared to conservative care, bullectomy was associated with a substantial improvement in FEV1 (Mean Difference: 0.48 L; 95% CI: 0.35 to 0.61) and a profound improvement in quality of life (SGRQ MD: -15.55; 95% CI: -20.21 to -10.89). However, this efficacy was counterbalanced by a nearly six-fold increase in the risk of major complications (Risk Ratio: 5.82; 95% CI: 2.98 to 11.37). Conclusion: Our synthesis suggests that for carefully selected patients, bullectomy offers superior physiological and quality-of-life outcomes over conservative management, but at the cost of significantly higher perioperative risk. These findings, derived from low-quality evidence, underscore the critical need for a highly individualized, multidisciplinary approach to patient selection and a thorough shared decision-making process.